Report of surgeries, their outcome and the thrombin generation assay in patients with Factor XI deficiency: A retrospective single‐centre study. Issue 2 (5th February 2022) - Désage, Stéphanie; Dargaud, Yesim; Meunier, Sandrine; Le Quellec, Sandra; Lienhart, Anne; Negrier, Claude; Nougier, Christophe; Rugeri, Lucia
Abstract: Background: In patients with FXI deficiency, the risk of surgery‐related bleeding is poorly correlated with plasma FXI activity (FXI:C); the latter can therefore not be used as a reliable predictor of bleeding in surgeries. Objectives: The aim of this retrospective study was to determine whether thrombin generation assay (TGA) could be used to evaluate the risk of surgery‐related bleeding in FXI‐deficient patients. TGA parameters were compared to FXI:C values, haemostatic treatments and surgical outcomes. Patients: All patients followed at the haemophilia treatment care centre (Lyon, France) with a FXI:C < 50IU/dL, and for whom a baseline TGA was performed between January 2014 and December 2019, were included. Results: Among the 175 surgeries reported herein in 49 patients, FXI concentrates were used for 11 (6%) surgeries and fresh frozen plasma was used for five (3%) surgeries; these surgeries were performed in patients with two or three impaired TGA parameters. No haemostatic treatment was prescribed for 119 (68%) surgeries. A surgery‐related bleeding occurred in 12 patients during 21 (12%) surgeries. Thrombin generation was significantly reduced or delayed in patients who reported surgery related‐bleeding. Among the 34 (68%) surgeries performed without haemostatic treatment in patients with three impaired TGA parameters, a surgery‐related bleeding was reported in 44% of cases (15 surgeries out of 34). Conclusion: The present study confirmed that TGA is an interesting laboratory test in FXI deficiency, for determining the bleeding risk and guiding the haemostatic management of surgeries, while taking into account the surgical bleeding risk and the history of bleeding.